Future supply of boreal forest ecosystem services is driven by management rather than by climate change - Triviño, María; Morán‐Ordoñez, Alejandra; Eyvindson, Kyle; Blattert, Clemens; Burgas, Daniel; Repo, Anna; Pohjanmies, Tähti; Brotons, Lluís; Snäll, Tord; Mönkkönen, Mikko
2022